The Two Umars as Inspiration for National Leaders: An Analysis of Prophetic Leadership Concepts - Wahyudin, Muhamad (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to identify and document the principles of prophetic leadership as applied by two significant figures in Islamic history, namely Umar ibn Khattab and Umar ibn Abdul Aziz. These principles are based on the Islamic political teachings of the Prophet Muhammad (peace be upon him), emphasizing justice, social welfare, honesty, and administrative efficiency. The research employs a qualitative approach through a literature review, which includes an analysis of historical documents, books, journals, and articles discussing Islamic politics and the leadership of these two figures. The findings of this study indicate that the prophetic leadership concepts practiced by the two Umars are highly relevant and can be effectively applied in modern leadership. These leadership principles provide solutions for contemporary challenges faced by today's leaders. They offer a model for creating governance or organizations that are more just, transparent, and focused on social welfare. Therefore, this research provides valuable historical insights and practical guidance for applying Islamic values in modern leadership.